PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN NILAI – NILAI KARAKTER SISWA DI SMP NEGERI 13 PEKANBARU - Anhar, Helvi Leriza; Arlizon, Raja; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : The challenge of globalization makes character building an important part of creating a high-quality people, but in fact it's even harder to implement. There are many schools and parents who want their students to receive high academic value, and ignore non-academic matters. Mostly, graduates include high graduates, many do not have strong and intelligent characters. The authors felt it necessary to study in a study with the title the influence of group guidance on the improvement of student character values. The purpose of the study was to know how the description of the character values of students before and after being given a group guidance service. In this research, use the experiment design method. Design of it’s research with a group pretest-posttest research method, a one-time pretest and posttest. Subject in this research is 20 students junior high school 13 Pekanbaru. The group guidance technique used is the way to provide information, the technique of providing information is the explanation by the group leader to the group members, the giving of information can be given by lecture, sincere, guidance board. Determination of the subject of this study is done by purposive sampling which means sampling technique with certain considerations in accordance with the required sample requirements. Data analysis technique used in this research is Wilcoxon test and Spearman rank test. After the implementation of group guidance services on the improvement of students character values, there is a positive influence of group guidance on the improvement of student character values.Keywords: Values of character, group guidance, peace loving, caring environment